QUANTUM METROLOGY WITHOUT QUANTUM ENTANGLEMENT - Datta, A; Shaji, A (2012)
We scrutinize the role of quantum entanglement in quantum metrology and discuss recent advances in nonlinear quantum metrology that allow improved scalings of the measurement precision with respect to the available resources. Such schemes can surpass the conventional Heisenberg limited scaling of 1/N of quantum enhanced metrology. Without investing in the preparation of entangled states, we review how systems with intrinsic nonlinearities such as BoseEinstein condensates and light-matter interfaces can provide improved scaling in single parameter estimation. © 2012 World Scientific Publishing Company.